2022
DOI: 10.1371/journal.pone.0278598
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila melanogaster attP40 docking site and derivatives are insertion mutations of msp-300

Abstract: The ɸC31 integrase system is widely used in Drosophila melanogaster to allow transgene targeting to specific loci. Over the years, flies bearing any of more than 100 attP docking sites have been constructed. One popular docking site, termed attP40, is located close to the Nesprin-1 orthologue msp-300 and lies upstream of certain msp-300 isoforms and within the first intron of others. Here we show that attP40 causes larval muscle nuclear clustering, which is a phenotype also conferred by msp-300 mutations. We a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…2022 ). In addition, this study also reported defects in muscle nuclei spacing in larval stages in the attP40 homozygous background, which phenocopies Msp300 mutants ( van der Graaf et al . 2022 ).…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…2022 ). In addition, this study also reported defects in muscle nuclei spacing in larval stages in the attP40 homozygous background, which phenocopies Msp300 mutants ( van der Graaf et al . 2022 ).…”
Section: Introductionsupporting
confidence: 61%
“…A recent study reported that flies homozygous for the attP40 -derived insertions had 50% reduction in Msp300 transcript levels and phenocopied the defects in larval muscle nuclei clustering in Msp300 mutants ( van der Graaf et al . 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations